PEMANFAATAN POTENSI DESA UNTUK MENINGKATKAN PENDAPATAN DESA TOTO UTARA KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Azis Rachman; Citra Dwi Setiyaningsih (LPPM Universitas Bina Mandiri Gorontalo, 2025)
This community service activity was carried out in North Toto Village, Tilongkabila District, Bone Bolango Regency, Gorontalo Province. The people of North Toto Village do not fully understand the importance of utilizing village potential to increase village income. The potentials in North Toto Village are: 1) natural potential; 2) cultural and traditional potential; 3) economic potential; and 4) the role of the government and the community.The purpose of this community service activity is to increase public awareness about the importance of utilizing village potential to increase village income, especially in North Toto Village.The implementation methods used in community service activities are: 1) problem identification; 2) forming a team of proposers; 3) observation of activity locations; 4) data collection; 5) identification of activity participants; 6) preparation of supporting materials, facilities and infrastructure; 7) delivery of materials; 8) development of local resources; 9) documentation; 10) reporting; and 11) publication. The result of this community service is that the people of North Toto Village really understand the importance of utilizing village potential to increase village income. The village government and the people of North Toto Village work together to develop the potentials that exist in North Toto Village in a sustainable and responsible way.